STUDI PERENCANAAN NORMALISASI SUNGAI KALI SONO DI KOTA MADIUN - Heremba, Sribanun Laila Sa’adah (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
PT. Bank Papua Cab. FakfakÂ Kali river is located in Madiun with 27,56 km2 large DAS Kali Sono. When the rain come,itcaused flood there. It is needed to solve the problem in which the capability to handle the waterdebitis low. The concept of planning and reconstructing system is flood handling system witharranging dike construction in all the left and right bank of the river.Nakayasu method is one method can be used to know the water debit in each 5 years based onthe arranged rainfall rate. The maximum debit from this accumulation is (Qtr 5) = 87.623 m/det2, soit is needed to reconstructing the river floor.After analize the water profil by using Standart FaseMethod by devide the flow into 58patok. The flow wide is plannedto get the fix profil. Dimensionwith the bank 1:1 is planned to build a dike with urugan ground. After controll the rembesan andaccumulate the stability, it shows savety dake result. From the savety wall analization with theworking force dan controlled to the rolle, movement, and ground pushment that happened to thesavety wall can fulfill the savety point which is appropriate with the legal savety.Keywords: River dimension arranging, dike